Ethics in publication - Wallace, Michael B.; Siersema, Peter D. (Endoscopy, 2015)
Publication of scientific manuscripts remains our core method of sharing knowledge and advanced scientific inquiry. Pressures to publish for reasons other than pure discovery have the potential to corrupt this process. The core principles of scientific ethics outlined above provide guidance on how to maintain the integrity of our scientific process. We, as journal editors, are committed to the advancement of scientific knowledge and the ethical process of publication. We do the best we can to make sure that the articles we publish fulfill all the criteria of a well-conducted study.